Groundswell Africa : A Deep Dive on Internal Climate Migration in Tanzania - Rigaud, Kanta Kumari; de Sherbinin, Alex; Jones, Bryan; Arora, Anmol; Adamo, Susana (World Bank, Washington, DC, 2021)
Between its natural wealth with diverse cultures, increasingly rapid urbanization, and some of the world’s most impressive wildlife, Tanzania strikes visitors as a country of diversity and dynamism. At the same time, the country is facing challenges from climate change that will put its people, policymakers, and ecosystems to a test. Migration has long been a strategy of Tanzanians to deal with adverse climatic conditions, but as this report illustrates, climate change will put further pressure on people to leave their homes and look for new opportunities elsewhere within the country’s borders. This study shows that Tanzania could see as many as 16.6 million internal climate migrants by 2050. Immediate, rapid and aggressive action on the cutting down emissions as a global community, and pursuing inclusive resilient development at the national level could bring down this scale of climate migration, on average, by about 27 percent.